Morphological and 18s rRNA sequencing of Euplotes sp.: a potential live feed for marine finfish larvae - Waludin, Shaidatul Nadia; Afand, Muhammad Mu’izzuddin; Mohammad Noor, Normawaty; Phang, Ing Chia; Kadowaki, Syusaku; Mukai, Yukinori (2016)
Euplotes is a ciliated protozoan that is highly diverse in size and species and has poten-tial to be used as live feed for marine feed larvae. This study was conducted to identify the suitable Euplotes candidate through molecular and morphological methods. Euplotes sp. was characterized by its morphological and 18S rRNA gene sequence. The selected Euplotes sp. was identified morphologically based on its unique present of infracillia-ture, dorsal-ventrally flattened, dorsally ridged and oval in shaped. For molecular identi-fication, samples of Euplotes sp. were collected and starved overnight before pelleted through centrifugation to provide closely packed Euplotes species. The extraction and amplification of genomic DNA of Euplotes sp. were done using REDExtract-N-AmpTM Tissue PCR Kit (Sigma). The phylogenetic analyses of the SSU RNA gene was ana-lyzed with evolutionary distance calculated using Kimura-two-parameter and further analyzed by using Maximum Likelihood (ML) and Neighbor-joining (NJ) with Coris julis (accession number HM049942.1) as an out group. The result showed Euplotes sp. is 96% related to Euplotes encysticus (accession number LN864512.1) and Euplotes no-vemcarinatus (accession number HM140407.1).